Commuting, Spatial Search and Labour Market Bargaining - Jos van Ommeren; Piet Rietveld (Tinbergen Institute, 2002)
We develop an equilibrium job search model in which employees incur endogenous commuting costs. This model leads to the following conclusions:1.Firms partially compensate workers for the incurred commuting costs.2.When workers have more bargaining power, they will receive less compensation for the incurred commuting costs.3.The average commuting costs are an increasing function of the productivity level of the workers, but a decreasing function of the unemployment benefit level.4.Given balanced growth, the average commuting costs are proportional to the average wage in the long run.5.Given balanced growth, the average commuting time is constant in the long run, but the average commuting distance and speed are increasing over time.
Keywords: 330; Suchtheorie; Verhandlungstheorie des Lohnes; Allgemeines Gleichgewicht; Theorie; Pendelverkehr